Urban characteristics, identities, and conservation of Chinatown Melbourne - Geng, Shiran; Chau, Hing-Wah; Jamei, Elmira; Vrcelj, Zora (Journal of Architecture and Urbanism, 2023)
Many unique ethnic enclaves have been established in Australia due to the country’s rich and diverse immigration history. Chinatown Melbourne is one of the oldest and most iconic examples that date back to the gold rush period in the 1850s. Previous studies have examined many aspects of the precinct, such as its architectural styles and demography shifts. However, there is a lack of research investigating the enclave’s urban characteristics and the consequent urban identity. This knowledge gap can lead to unfeasible heritage conservation decisions with a lack of emphasis on the precinct’s unique identity. Hence, this study aims to scrutinize the precinct’s past urban evolution and its present characteristics to better understand its heritage value and enhance future urban policies. Qualitative data are collected using archival and literature review, map analysis, and field observation. Overall, by elucidating Chinatown Melbourne’s urban characteristics and key urban movements, the study depicts the precinct’s identity, addressing elements like the main, laneway, gateway, and public space. The output of the research provides insights into how future heritage policies and initiatives can benefit from the case study in enhancing heritage protection and sustaining its urban identity. Further research is recommended to incorporate quantitative research methods and compare results with this study’s findings.